1991
DOI: 10.1128/aac.35.1.141
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial activities of PD 131628, a new 1,8-naphthyridine anti-infective agent

Abstract: PD 131628 is a new aminopyrrolidine-substituted fluorocyclopropyl naphthyridine quinolone which possesses high in vitro activity against a wide spectrum of bacterial species. The MICs for .90% of strains were 0.125 to 0.25 ,ug/ml for staphylococci, Streptococcus pyogenes, and S. pneumoniae; 0.5 ,ug/ml for S. agalactiae and Enterococcus faecalis; 0.125 jug/ml for members of the family Enterobacteriaceae and Acinetobacter spp.; 0.5 ,Lg/mI for Pseudomonas aeruginosa; and <0.03 ,ug/ml for Haemophilus influenzae, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…Activity was greatest in strains for which ciprofloxacin MICs were s2.0 ,ug/ml. Clinafloxacin and PD 131628 are two new experimental fluoroquinolones with expanded activity against gram-positive and gram-negative organisms, including members of the family Enterobacteriaceae, Streptococcus pneumoniae, and some anaerobes (5,6,9,12,16). This study confirms the increased activity against X. maltophilia reported by other workers (5,6,8,16).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Activity was greatest in strains for which ciprofloxacin MICs were s2.0 ,ug/ml. Clinafloxacin and PD 131628 are two new experimental fluoroquinolones with expanded activity against gram-positive and gram-negative organisms, including members of the family Enterobacteriaceae, Streptococcus pneumoniae, and some anaerobes (5,6,9,12,16). This study confirms the increased activity against X. maltophilia reported by other workers (5,6,8,16).…”
supporting
confidence: 80%
“…Available quinolones such as ciprofloxacin and ofloxacin are marginally active, with MICs for susceptible isolates clustering around the breakpoint (1,4,9,(12)(13)(14). Clinafloxacin (CI-960, PD 127391) and PD 131628 (the active component of the prodrug CI-990) are two new fluoroquinolones with improved activity against gram-positive cocci, gramnegative nonfermenters, and anaerobes (5,6,8,9,12,16). This study compared the activities of clinafloxacin, PD 131628, two other experimental broad-spectrum fluoroquinolones (PD 138312 and PD 140248) (2, 7), ciprofloxacin, and ofloxacin against 123 clinical isolates of X maltophilia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, industry has attempted to synthesize new compounds with improved antianaerobic activity (5). We evaluated the activities of seven fluoroquinolone compounds against 290 recent clinical anaerobic isolates and three American Type Culture Collection (ATCC) strains.…”
mentioning
confidence: 99%
“…The remaining fluoroquinolones had little activity against this organism. Pharmacokinetic studies have shown that CI-990's active drug PD 131628 is released rapidly upon oral or parenteral administration in experimental animals and has excellent absorption and distribution properties [19].…”
Section: Resultsmentioning
confidence: 99%